Cooking for documenta IX. - Ippel, Willemien (Kassel, 1992)
Durham, Jimmie ; Simoni, Mariella ; Brey, Isabel ; Brey, Ricardo ; Pistoletto, Maria ; Pistoletto, Christina ; Kosuth, Joseph ; Cabrita Reis, Pedro ; Kogler, Peter ; Katase, Kazuo ; Adelmann, Irene ; Hunstein, Heinrich ; Takeoka, Yuji ; Cerbai, Roberto ; Zvezdochotov, Constantin ; Geong Byung, Yook
1992/04/08 - 1992/06/06
publ. SMAK : zie kast leeszaal
boek